Early and late coronary stent thrombosis of sirolimus-eluting and paclitaxel-eluting stents in routine clinical practice: data from a large two-institutional cohort study - Daemen, Joost; Wenaweser, Peter; Tsuchida, Keiichi; Abrecht, Linda; Vaina, Sophia; Morger, Cyrill; Kukreja, Neville; Jüni, Peter; Sianos, Georgios; Hellige, Gerrit; van Domburg, Ron T; Hess, Otto M; et al. (The Lancet (British edition), 2007)
Stent thrombosis is a safety concern associated with use of drug-eluting stents. Little is known about occurrence of stent thrombosis more than 1 year after implantation of such stents. Between April, 2002, and Dec, 2005, 8146 patients underwent percutaneous coronary intervention with sirolimus-eluting stents (SES; n=3823) or paclitaxel-eluting stents (PES; n=4323) at two academic hospitals. We assessed data from this group to ascertain the incidence, time course, and correlates of stent thrombosis, and the differences between early (0–30 days) and late (>30 days) stent thrombosis and between SES and PES. Angiographically documented stent thrombosis occurred in 152 patients (incidence density 1·3 per 100 person-years; cumulative incidence at 3 years 2·9%). Early stent thrombosis was noted in 91 (60%) patients, and late stent thrombosis in 61 (40%) patients. Late stent thrombosis occurred steadily at a constant rate of 0·6% per year up to 3 years after stent implantation. Incidence of early stent thrombosis was similar for SES (1·1%) and PES (1·3%), but late stent thrombosis was more frequent with PES (1·8%) than with SES (1·4%; p=0·031). At the time of stent thrombosis, dual antiplatelet therapy was being taken by 87% (early) and 23% (late) of patients (p<0·0001). Independent predictors of overall stent thrombosis were acute coronary syndrome at presentation (hazard ratio 2·28, 95% CI 1·29–4·03) and diabetes (2·03, 1·07–3·83). Late stent thrombosis was encountered steadily with no evidence of diminution up to 3 years of follow-up. Early and late stent thrombosis were observed with SES and with PES. Acute coronary syndrome at presentation and diabetes were independent predictors of stent thrombosis.